The effect of process parameters on the material position of dissimilar friction stir welded AA2024-T3/5754-H22 joints - (:unkn) unknown (Slovenska Akademia Vied, 2017)
In this study, the effect of process parameters on the material position, microstructural and mechanical properties such as microhardness distribution, ultimate tensile strength and optical microscope of the friction stir welded dissimilar joints was studied. The effects of the material positioning, the tool rotational speed and tool traverse speed as well as tool tilt angle on the joint strength were investigated. The experimental results showed that the positioning of the sheets played an important role in the strength of the joints. The joint strength was higher when the AA2024 sheet was positioned on the retreating side of the joint. The optimum test condition was obtained at a tool rotational speed of 900 rpm and a tool traverse speed of 45 mm min-1. The microhardness in the advancing side of the heat affected zone/base metal interface zone of AA5754-H22 was found to be minimum, where the welded joints failed during the tensile studies.
Keywords: Dissimilar weld; Friction stir welding; Mechanical properties; Microhardness